Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Produktivitas Karyawan Pada PT. Kaltim Nusa Etika Sangatta - Rizkiawan; Arbayah; Riana, Ausy (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The purpose of this study is to determine the influence of motivation and work environment on employee productivity at PT. Kaltim Nusa Etika Sangatta. The data collection method in this study is a questionnaire using a census or saturation sampling technique as well as a population and sample of 34 respondents. Based on the results of this study, it shows that partially motivation has a positive and significant effect on employee productivity at PT. Kaltim Nusa Etika Sangatta, the work environment has a positive and insignificant effect on employee productivity at PT. Kaltim Nusa Etika Sangatta, as well as simultaneously motivation and work environment have a positive and significant effect on the productivity of employees of PT. Kaltim Nusa Etika Sangatta. The Coefficient of Determination (R2) of 0.456 (45.6%) can be interpreted that motivation (X1) and work environment (X2) explain the variation of employee productivity variables (Y) by 45.6%.